How Digital Transformation Impacting the Product Innovation - Satyani, Fatma; Sundiman, Didi (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2021)
In the last decade, the emergence of various set of novel digital technologies has transformed innovation and entrepreneurship very significantly. One of the reasons why organizations are shifting to digital transformation is the velocity of volatility in markets. The research objective is to identify the impact of digital transformations' key attributes on an organization's innovation specifically in terms of creating new products and the role of different variables on this capability. Researcher used systematic literature review as the method. The results show that the transformation of digital is more than just upgrading technologies. And researcher found out the main pillars of digital transformation, which will be mentioned in the article. In the end, the researcher provides recommendation for future research.